Penobscot materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Gordon, G. B. (George Byron), 1870-1927; Day, Gordon M.; Gandy, Ethel; Eckstorm, Fannie Hardy, 1865-1946; Swadesh, Morris, 1909-1967; Voegelin, C. F. (Charles Frederick), 1906-1986; Wilder, Harris Hawthorne, 1864-1928; Nassau, Robert Hamill, 1835-1921; Osgood, Cornelius, 1905-1985; Ranco, Dorothy; Princess Pretty Woman; et al. (1908)
Materials relating to Speck's study of Penobscot language, history, and culture, and his preparation of his book Penobscot Man. This includes several folders of Speck's field notes, notes organized around specific topics (including data not used in Speck's published works), copies and drafts of lectures and essays, correspondence, etc. Topics include Penobscot social organization, calendar system, house furnishings, hunting morality, animal lore, religion, art, sayings, alphabet, counting and measuring, canoe-making, face-painting, texts with interlineal translations, and "Bird Lore of the Northern Indians" (a faculty public lecture at the University of Pennsylvania). Additionally, significant correspondence concerns the preparation, expenses, dissemination, and reception of his Penobscot publications. Other topics of correspondence include Ethel Gandy's monograph on Penobscot art; names of chiefs and their clans; "clown" performances outside of the southwest among the Penobscot, Iroquois [Haudenosaunee], Abenaki, and Delaware; place names; the relationship of Penobscot-Mohegan and Mahican; a comparison of Zuni-Navajo and Red Paint; Tutelo. There is a particularly large folder of Speck's miscellaneous Penobscot notes containing both a variety of notes and correspondence from Penobscot consultants as well as non-Native colleagues. These include letters from Roland E. Nelson (Needahbeh, Penobscot) concerning drum for exhibit; letters from Nelson, Franz Boas, John M. Cooper, William B. Goodwin, E. V. McCollum, and J. Dyneley Prince, all concerning Penobscot Man; Clifford P. Wilson concerning moosehair embroidery; Edward Reman concerning Norse influence on Penobscot; Carrie A. Lyford concerning moose-wool controversy and Ann Stimson's report; Ann Stimson, letter of thanks; Henry Noyes Otis concerning genealogy of Indians named Sias on Cape Cod (Speck marked this Penobscot); Princess Pretty Woman (Passamaquoddy) concerning her dress (apparently at the Penn Museum); Dorothy Ranco (Penobscot) concerning Princess Pretty ...